EXTRACTION OF SEA GRAPE (Caulerpa lentillifera) BY MACERATING GRADE WITH SOLVENTS OF DIFFERENT POLARITY - Reza Saputra; Andarini Diharmi; Edison Edison (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTCaulerpa lentillifera is one of the potential seaweed commodities and is known as sea grapes. This study aims to determine the maceration extraction technique of C. lentillifera in stages using different polarity solvents. The method used in this research is experimental, namely the extraction of C. lentillifera by graded maceration using solvents of different polarity consisting of n-hexane (non polar), ethyl acetate (semi polar), and methanol (polar) with a comparison of sample to solvent (1:3 w/v) for 72 hours. The extract was filtered with whatman paper and evaporated using a rotary vacuum evaporator at a temperature of ± 40°C to obtain a thick extract. Parameter analysis calculation of yield of each extract produced from different solvents. The results showed that the average yield of each extract of n-hexane, ethyl acetate, and methanol was 0.36%, respectively; 0.39%; and 0.42%. The lowest yield was from n-hexane extract and the highest was methanol extract.Keywords:Sea grape; C. lentillifera; extraction method; graded maceration